HIGHER MADRASAHS OPERATING IN THE BUKHARA EMIRATE (END OF THE 19TH CENTURY – EARLY 20TH CENTURY) (International Educators Conference, 2025)
This article provides information about the higher madrasahs that operated in the Bukhara Emirate and their significance. It discusses the historical and educational impact of these institutions on the region and the development of Islamic education in Central Asia.